URGENSI PERUBAHAN PROVINSI NTT MENJADI DAERAH KHUSUS PROVINSI KEPULAUAN DAN PERBATASAN NEGARA SERTA IMPLIKASI YURIDIS DALAM TATA PEMERINTAHAN DAERAHNYA - Septiandhito, Teodorus; Tuba Helan, Yohanes G; Stefanus, Kotan Y (Petitum Law Journal, 2023)
The Province of East Nusa Tenggara (NTT) as a part of the Unitary State of the Republic of Indonesia has different characteristics from other provinces in Indonesia, geographically NTT is an archipelagic province consisting of a combination of large and small islands separated by sea. Meanwhile, from a national strategic perspective, NTT is a border area with other countries, sea borders with Australia and land borders with the Democratic State of Timor Leste (RDTL), and specifically within the NTT Province area there is the Oecusee Enclave which is part of RDTL. The conditions in NTT, which are very unique and not found in other provinces in Indonesia, have been a factor in the regional government in NTT not being optimal in carrying out government tasks. The effectiveness and efficiency of government, the high costs of government and development are the main obstacles and challenges faced and have made NTT Province one of the disadvantaged and poorest regions in Indonesia. To overcome the various challenges of regional governance in NTT Province, the implementation of asymmetric decentralization in the form of granting special status to NTT Province based on its geographical characteristics as an islands region and its strategic position as a state border is seen as the right solution to develop and direct NTT Province to be more competitive and able to keep pace with other provinces in Indonesia while strengthening Indonesia's outermost regions which are gateways to other countries. This legal research shows that basically the Indonesian constitution and the development of regional governance and national politics make it possible to provide asymmetric decentralization for the NTT Province to become a Special Province of Islands and National Borders. The implementation of asymmetric decentralization will have juridical implications in several areas of regional government in NTT, but ultimately aims to improve the welfare of the people of NTT which is the outermost fence on the southern side of Indonesia.